Long-Term Effects of Maternal Deprivation on Redox Regulation in Rat Brain: Involvement of NADPH Oxidase. (20th March 2017) - Marković, Branka; Radonjić, Nevena V.; Jevtić, Gordana; Stojković, Tihomir; Velimirović, Milica; Aksić, Milan; Poleksić, Joko; Nikolić, Tatjana; Aleksić, Dubravka; Radonjić, Vidosava; Filipović, Branislav; Petronijević, Nataša D.
Abstract : Maternal deprivation (MD) causes perinatal stress, with subsequent behavioral changes which resemble the symptoms of schizophrenia. The NADPH oxidase is one of the major generators of reactive oxygen species, known to play a role in stress response in different tissues. The aim of this study was to elucidate the long-term effects of MD on the expression of NADPH oxidase subunits (g p 91 p h o x, p 22 p h o x, p 67 p h o x, p 47 p h o x, and p 40 p h o x ). Activities of cytochrome C oxidase and respiratory chain Complex I, as well as the oxidative stress parameters using appropriate spectrophotometric techniques were analyzed. Nine-day-old Wistar rats were exposed to a 24 h maternal deprivation and sacrificed at young adult age. The structures affected by perinatal stress, cortex, hippocampus, thalamus, and caudate nuclei were investigated. The most prominent findings were increased expressions of g p 91 p h o x in the cortex and hippocampus, increased expression of p 22 p h o x and p 40 p h o x, and decreased expression of g p 91 p h o x, p 22 p h o x, and p 47 p h o x in the caudate nuclei. Complex I activity was increased in all structures except cortex. Content of reduced glutathione was decreased in all sections while region-specific changes of other oxidative stress parameters were found. Our results indicate the presence of long-term redox alterations in MD rats.